Drainage Density and Its Controlling Factors on the Eastern Margin of the Qinghai–Tibet Plateau - Gao, Hongshan; Liu, Fenliang; Yan, Tianqi; Qin, Lin; Li, Zongmeng (Frontiers in Earth Science, 2022)
The drainage density(Dd) is an important index to show the fluvial geomorphology. The study on Dd is helpful to understand evolution of the whole hydrological and geomorphic process. Based on SRTM 90 m digital elevation model, drainage network of basins along the eastern margin of the Qinghai-Tibet Plateau is extracted using a terrain morphology-based method in ArcGIS 10.3, and Dd is calculated. The sptatial characteristics of Dd are analyzed, and the relationship between Dd and its influencing factors, e.g. the topography, precipitation and vegetation coverage are explored. Our results show that terrains with a plan curvature ≥ 3 can represent the channels in the study area. Dd ranges from 2.5 to 0.1 km/km2, increases first and then decreases from north to south on the eastern margin of the Qinghai-Tibet Plateau. Dd decreases with increasing average slope and average local relief. On the low-relief planation surfaces, Dd increases with increasing altitude, while on the rugged mountainous above planation surfaces, Dd decreases rapidly with increasing altitude. Dd firstly increased and then decreased with increasing MAP(mean annual precipitation) and NDVI(normalized difference vegetation index), and Dd reaches to a maximum in the Western Qinling Mountains with a semi-arid environment, indicating that Dd in different climatic regions of the eastern margin of the Qinghai-Tibet Plateau was mainly controlled by precipitation and vegetation.